Temporal Immediacy: A Two-System Theory of Mind for Understanding and Changing Health Behaviors. Issue 2 (March 2018) - Cook, Paul F.; Schmiege, Sarah J.; Reeder, Blaine; Horton-Deutsch, Sara; Lowe, Nancy K.; Meek, Paula
Abstract : Background: Health promotion and chronic disease management both require behavior change, but people find it hard to change behavior despite having good intentions. The problem arises because patients' narratives about experiences and intentions are filtered through memory and language. These narratives inaccurately reflect intuitive decision-making or actual behaviors. Objectives: We propose a principle—temporal immediacy—as a moderator variable that explains which of two mental systems (narrative or intuitive) will be activated in any given situation. We reviewed multiple scientific areas to test temporal immediacy as an explanation for findings. Methods: In an iterative process, we used evidence from philosophy, cognitive neuroscience, behavioral economics, symptom science, and ecological momentary assessment to develop our theoretical perspective. These perspectives each suggest two cognitive systems that differ in their level of temporal immediacy: an intuitive system that produces behavior in response to everyday states and a narrative system that interprets and explains these experiences after the fact. Findings: Writers from Plato onward describe two competing influences on behavior—often with moral overtones. People tend to identify with the language-based narrative system and blame unhelpful results on the less accessible intuitive system, but neither is completely rational, and the intuitive system has strengths based on speed and serial processing. The systems differ based on temporal immediacy—the description of an experience as either "now" or "usually"—with the intuitive system generating behaviors automatically in real time and the narrative system producing beliefs about the past or future. Discussion: The principle of temporal immediacy is a tool to integrate nursing science with other disciplinary traditions and to improve research and practice. Interventions should build on each system's strengths, rather than treating the intuitive system as a barrier for the narrative system to overcome. Nursing researchers need to study the roles and effects of both systems.